The English language : a linguistic history - Brinton, Laurel J.; Arnovick, Leslie K., 1957- (Don Mills, Ontario : Oxford University Press, 2017)
"The English Language: A Linguistic History surveys the development of the English language from its Indo-European past to the present day. It covers the entire history of the English language beginning with its prehistoric origins in Proto-Indo-European and includes thorough coverage of its four major periods: Old English, Middle English, Early Modern English, and Modern English. The third edition features enhanced discussion of the socio-historical and cultural contexts of the English language in the new "Language in Context" features in each chapter. Brief timelines of historical events also now appear at the beginning of relevant chapters, supplementing the comprehensive timeline (linguistic, literary, historical, and social) found in the appendices. Discussion of new approaches to the history of English, such as historical pragmatics and historical sociolinguistics, have been added or expanded along with new debates, such as the current work on the Proto-Indo-Europeans or the status of English as a global language or second language. A new appendix includes an anthology of specimen texts from the four major periods of English, chosen for their use of colloquial and non-literary language" --
Studying the history of English -- Sounds and sound change in English -- Causes and mechanism of language change -- The Indo-European language family and proto-Indo-European -- Germanic and the development of old English -- The words and sounds of old English -- The grammar of old English -- The rise of middle English: words and sounds -- The grammar of middle English and the rise of a written standard -- The words, sounds, and inflections of early modern English -- Early modern English verbal constructions and Eighteen-century prescriptivism -- Modern English -- Varieties of English.
Previous edition: 2011.
Includes bibliographical references (pages 602-608) and index.
ENH
Keywords: English language -- History -- Textbooks; English language -- History; English language